Effects of different nitrogen treatments on the growth and nitrogen metabolism of Machilus thunbergii seedlings - Shi, Fenghou; Feng, Haoyi; Li, Xiaojing; Zhang, Yuhui; Bai, Yanan; Tong, Boqiang; Lu, Yizeng (Frontiers in Plant Science, 2025)
IntroductionAs a native tree species in China, Machilus thunbergii is highly responsive to nitrogen fertilization. However, related studies are scarce. This research seeks to elucidate how different nitrogen fertilizers affect its growth and nitrogen metabolism across different growth stages, thereby determining the most suitable type and establishing a scientific foundation for its fertilization.MethodsThis study aimed to investigate the effects of topdressing with different nitrogen fertilizers on the growth and nitrogen metabolism of M. thunbergii seedlings, with the goal of providing a scientific basis for optimized nitrogen fertilization management in M. thunbergii cultivation. The study used 3-year-old M. thunbergii seedlings as the material, and the fertilization rate was 3 g per seedling. The experiment was conducted in a one-way randomized block design with four treatments, including the control treatment and three nitrogen fertilizer treatments: urea (amide nitrogen fertilizer), ammonium sulfate (ammonium nitrogen fertilizer), and sodium nitrate (nitrate nitrogen fertilizer). From the start of the experiment, the branch and leaf morphology, the height growth, and the basal diameter growth of the seedlings in each treatment were monitored periodically. The activities of the nitrogen-metabolizing enzymes, such as nitrate reductase, glutamine synthetase, glutamate synthetase, and glutamate dehydrogenase, in the leaves were also measured. At growth cessation, all treatments were evaluated for biomass production, root morphological characteristics, and total nitrogen content in different plant parts (i.e., roots, stems, and leaves).ResultsDue to the high nitrogen content in the cultivation substrate, the application of the different nitrogen fertilizers induced varying levels of fertilizer injury. Temporal analysis revealed that the growth inhibition was not uniform across stages. While all nitrogen treatments ultimately suppressed the overall height and diameter growth compared with the control, the timing and the intensity of these effects varied. For instance, the urea treatment initially showed less inhibition, whereas the sodium nitrate treatment consistently exhibited the strongest inhibitory effect throughout the experiment. Similarly, the promotion of nitrogen metabolism enzyme activity by the different fertilizers also displayed distinct temporal patterns, with peaks occurring at different measurement points. All nitrogen treatments increased the nitrogen content in the root, stem, and leaf parts, but decreased the nitrogen translocation efficiency of M. thunbergii seedlings. All nitrogen treatments increased the nitrogen accumulation in the roots and stems of seedlings. Urea treatment enhanced foliar nitrogen accumulation, whereas both the ammonium sulfate and sodium nitrate treatments reduced foliar nitrogen accumulation.ConclusionAll three nitrogen treatments significantly influenced both the growth and physiological indices of M. thunbergii seedlings. While generally enhancing the nitrogen metabolism and accumulation, improper selection of fertilizer types or excessive application rates elevated the tissue nitrogen concentration, inducing phytotoxic effects that ultimately inhibited seedling growth. In this research, sodium nitrate had the greatest toxic effect on M. thunbergii seedlings, followed by ammonium sulfate and urea. Among the nitrogen fertilizers tested, urea proved superior at an application rate of 3 g per plant for 3-year-old M. thunbergii seedlings.